Pharmacokinetic–pharmacodynamic modelling of neutrophil response to G‐CSF in healthy subjects and patients with chemotherapy‐induced neutropenia - Melhem, Murad; Delor, Isabelle; Pérez‐Ruixo, Juan Jose; Harrold, John; Chow, Andrew; Wu, Liviawati; Jacqmin, Philippe (British journal of clinical pharmacology, 2018)
Aim The objective of the present study was to use pharmacokinetic–pharmacodynamic modelling to characterize the effects of chemotherapy on the granulopoietic system and to predict the absolute neutrophil counts (ANCs) for patients with chemotherapy‐induced neutropenia treated with filgrastim and pegfilgrastim. Methods Data were extracted from 10 phase I–III studies conducted in 110 healthy adults, and 618 adult and 52 paediatric patients on chemotherapy following administration of filgrastim or pegfilgrastim. The structural model accounted for ANC dynamics and the effects of filgrastim and pegfilgrastim, chemotherapy and corticosteroids. The impact of neutrophils on drug disposition was based on a drug receptor–binding model that assumed quasi‐equilibrium and stimulation of the production and maturation of neutrophils upon treatment. The chemotherapy and corticosteroid effects were represented by kinetic–pharmacodynamic‐type models, where chemotherapy stimulated elimination of neutrophil precursors at the mitotic stage, and corticosteroids stimulated neutrophil production. Results The systemic half‐lives of filgrastim (2.6 h) and pegfilgrastim (10.1 h) were as expected. The effective half‐life of chemotherapy was 9.6 h, with a 2‐day killing effect. The rate of receptor elimination from mitotic compartments exhibited extreme interindividual variability (% coefficient of variation >200), suggesting marked differences in sensitivity to chemotherapy effects on ANCs. The stimulatory effects of pegfilgrastim were significantly greater than those of filgrastim. Model qualification confirmed the predictive capability of this model. Conclusion This qualified model simulates the time course of ANC in the absence or presence of chemotherapy and predicts nadir, time to nadir and time of recovery from different grades of neutropenia upon treatment with filgrastim and pegfilgrastim.